Meningkatkan Keaktifan dan Hasil Belajar Pada Mata Pelajaran CNC Melalui Aplikasi Swansoft CNC Simulator - Muhammad Jefri Pradana; Samidjo Samidjo; Samsul Hadi (JURNAL VOKASI DEWANTARA (JVD), 2022)
This research sought to increase the activeness and learning achievement of students at Mechanical Engineering Vocational School through the use of swansoft CNC simulator application on CNC subject. This research implemented classroom action research design, consisting of 3 cycles. Each cycle consisted of four stages of planning, implementing, observing, and reflecting. The subjects involved were twelfth grade students of Mechanical Engineering Vocational School. Observation sheets and multiple-choice tests were used to collect data which were then analyzed using descriptive analysis technique. The research results showed that the use of swansoft CNC simulator could increase the activeness and learning achievement of twelfth grade students of Mechanical Engineering Vocational School. Learning activeness increased and could be seen from the first cycle of 50.25% in less active category, to the second cycle of 54.75% in fairly active category, and finally the third cycle of 68% in active category. Learning achievement increased and it could be seen from test results that in cycle I there were 64% of students who reached the minimum standard score of 75, and the number increased in cycle II to 72%, and increased further in cycle III to 80%.